Pre-and postcalving supplementation of multinutrient blocks on lactation and reproductive performances of grazing Bali cows - Belli, H.L.L (Indonesian Animal Sciences Society, 2006)
The influence of multinutrient blocks during pre and postcalving on lactation and reproductive performances of Bali cows were evaluated. Seventeen multiparous pregnant cows with body condition score (BCS) 1 to 2, approximately 90 d before the expected date of calving, were divided randomly into groups A (n=9) and B (n=8), and were grazed on the native pasture as a basal diet, while those of Group B received 1.25 kg multinutrient blocks, whose constituent was as follows (%): molasses (28), urea (5), coconut cake (15), fishmeal (5), rice bran (25), lime (8.5), salt (7.5), grit (5) and ultramineral (1). Cows were weighed and assessed for BCS (on a five-point scale) every two weeks, commencing at 12 weeks prior to calving, within 24 h after calving up to 16 weeks after calving. Milk production and composition were assessed by the weigh-suckle-weigh technique at four times i.e. 2, 4, 8 and 12 weeks after calving. Suckling behaviour i.e. frequency of suckling, duration of nursing and total min nursed were observed 6 times in the course of lactation at weekly intervals commencing at 1 week after calving. Calf birth weight was measured within 24 h after calving and continued at weekly intervals until 12 weeks of age. Uterine involution was determined by rectal palpation at 7 d postcalving. The interval from calving to first estrus was monitored by estrus observation twice a day. Conception at first service was assessed by pregnancy diagnosis 45 to 60 d after insemination. Cows fed multinutrient blocks supplement had higher liveweight, BCS throughout the experiment. The cows produced significantly more milk and had higher growth rates of the calves than the unsupplemented cows. The mean values of the characteristics of suckling were influenced by supplementation. The rate of uterine involution and conception to first service were similar in the two treatment groups, but interval from calving to the exhibition of the first estrus was shorter in supplemented cows. Key Words: Supplementation, Multinutrient Block, Bali Cows